A greener approach to byproducts from the production of heat-treated poplar wood: Analysis of volatile organic compound emissions and antimicrobial activities of its condensate. (10th March 2019) - Chu, Demiao; Zhang, Xinyu; Mu, Jun; Avramidis, Stavros; Xue, Lei; Li, Yushuang
Abstract: Although many properties of plantation wood are greatly enhanced by heat treatment, large quantities of volatile organic compounds (VOCs) are released from this process, resulting in potential problems for the environment and human health. Volatile byproducts were collected from Populus tomentosa wood that was treated at 160, 180, 200, and 220 °C for 2 h. The VOC gases were partly collected at the heating, holding, and cooling stages of the process and were then analyzed by gas chromatography-mass spectrometry and thermogravimetry. The results show that over 90% of the volatiles from the first and third stages were alkane compounds. The mass losses in the heating and holding stages were almost at the same level, and the liquid byproduct contained approximately 48% phenolic products at 160 °C. The volatiles at 180 °C were mainly alkanes, terpenes, and aromatic compounds, and the absolute amount of VOCs released in the holding stage was much higher than that in the heating stage. The concentrations of phenols and ketones in the liquid byproducts decreased when the treatment temperature was increased, and more complex chemicals such as N-containing compounds emerged. Ester and aromatic compounds increased with the treatment temperature. The condensate collected at 160 °C exhibited considerable biological activity in the bacterial and mildew resistance tests. These results suggest that thermally treated byproducts can be turned into wood preservatives, which would also make the wood heat treatment cleaner. Highlights: The byproducts from different temperatures and stages were analyzed. The condensate was demonstrated to possess potent biological activity. Collecting VOCs would avoid air pollution, and condensates have potential value.